Diffuse hyperpigmentation in children: description of three cases and review of the literature. - Ballal, S.; Prathibha , J.P.; Sequeira, V.E.; Augustine, M.; Poornima, R.N. (European Journal of Pediatric Dermatology, 2025)
Diffuse hyperpigmentation in the pediatric population is a rare condition with multiple causes. We present three cases of diffuse hyperpigmentation in infants, each with a different underlying diagnosis: primary adrenal insufficiency, familial glucocorticoid deficiency, and neonatal hemochromatosis. All three entities presented with diffuse hyperpigmentation in the neonatal-infantile period, along with systemic features and abnormal laboratory parameters. Early diagnosis and appropriate treatment are crucial for these conditions, as they can have significant health consequences.